SIDELINED SEASHELLS: REAPPRAISAL OF THE MIDDLE TRIASSIC AMMONOIDS OF SAMOBOR AND ŽUMBERAK MTS. (NORTH-WESTERN CROATIA) AND THEIR SYSTEMATICS AND BIOSTRATIGRAPHIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Basinal Middle Triassic successions of the Samobor and Žumberak Mts. (north-western Croatia) have historically produced fossils of ammonoids. These finds have, however, largely been neglected in the later literature. This paper describes and redescribes a large collection of ammonoids, most of which were collected by previous researchers throughout the 20th century. Aside from the detailed taxonomic descriptions and revisions, several taxa previously unknown from these localities were identified. Of the species whose holotypes were designated at the Gregruć Breg locality, some are found to be dubious, with validity of other remaining inconclusive and a single taxon, Eoprotrachyceras dorae comb. nov., being treated as valid. Certain Middle Triassic ammonoid genera may also require future comprehensive revisions. A preliminary, modified ammonoid zonal/sub-zonal scheme for the Ladinian of the Tethyan province is proposed, to be inclusive of most of the data from the literature. The need for improvement of the subdivision of this stage is recognized. Based on ammonoids, condensed red nodular limestones of the Gregurić Breg locality (Samobor Mts.) most likely span the Avisianum subzone (upper Illyrian) – Longobardicum subzone (“middle” Longobardian), indicating that subsidence began in the earlier part of the Illyrian. At Mt. Žumberak, scant ammonoid remains indicate that the upper, limestone-rich portion of this succession spans at least the Avisianum subzone (upper Illyrian) – Longobardicum subzone (“middle” Longobardian), but additional data is needed for drawing more robust conclusions. Overall, the timing of basinal deposition is well correlated between Gregurić Breg and Žumberak localities (lower Illyrian – upper Longobardian).